2020
DOI: 10.1002/stem.3207
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cxcr5 alters neuroblast proliferation and migration in the aged brain

Abstract: Neurogenesis, the production of new neurons from neural stem cells, dramatically decreases during aging concomitantly with increased inflammation both systemically and in the brain. However, the precise role of inflammation and whether local or systemic factors drive the neurogenic decline during aging is poorly understood. Here, we identify CXCR5/5/CXCL13 signaling as a novel regulator of neurogenesis in the aged brain. The chemokine Cxcl13 was found to be upregulated in the brain during aging. Loss of its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Cell adhesion emerged as a hallmark of NSC aging in our study. The migratory properties of neuroblasts has started to be examined with age [44][45][46][47] and in the context of innervating distal tumors 73 . But the changes in migration and adhesion in quiescent and activated NSCs, the upstream NSC populations that give rise to migratory neuroblasts, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cell adhesion emerged as a hallmark of NSC aging in our study. The migratory properties of neuroblasts has started to be examined with age [44][45][46][47] and in the context of innervating distal tumors 73 . But the changes in migration and adhesion in quiescent and activated NSCs, the upstream NSC populations that give rise to migratory neuroblasts, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many of these age-related chromatin changes occur in regulatory regions of cell adhesion and migration genes. The migratory properties of NSCs and neuroblasts has started to be examined with age [55][56][57][58][59] and in the context of innervating distal tumors 88 . Recent live-cell imaging of SVZ wholemounts showed that aNSC and NPC migration distance and speed decreased with age 59 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During normal aging, due to the decline in the metabolic function of neurons and astrocytes, accumulation of abnormal proteins and DNA breakage, lipids and other macromolecular substances are gradually oxidized and cannot be degraded by the lysosomes. In addition, the destruction of proteins during aging increases and affects the phagocytosis of cells, which leads to the accumulation of denatured proteins in lysosomes [35, 36]. Several studies have shown that LBPs can promote the neural differentiation of neural stem cells and inhibit the abnormal differentiation of glial cells, thereby improving brain function during aging and in neurodegenerative diseases, such as AD and macular degeneration.…”
Section: Neuroprotective Effect and Mechanism Of Lbpsmentioning
confidence: 99%